CHEMOPROPHYLAXIS IN SURGICAL SITE INFECTION: IS IT REALLY NECESSARY - Faheem, Fraz (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the need of using chemoprophylaxis for surgical site infection (SSI) in clean and clean contaminated general surgical procedures and to compare the efficacy of monotherapy using Cefuroxime and combination therapy using Triple Regime. Methodology: This prospective randomized single blinded study included 534 patients. We included all ASA Grade 1 or 2, immunocompetent patients undergoing clean or clean contaminated surgery. Group A received placebo. Group B received single dose Cefuroxime 750mg iv preoperatively and Group C received triple regime. Any SSI was recorded which occurred up to 30 days post operatively. Results: The three groups were well matched demographically. (p value < 0.05). Group A (43 patients) was terminated early due to unacceptably high rate of wound infection. Amongst the remaining 491 patients, 247 were randomized to Group B and 244 to Group C. Among the clean cases Group C showed a lower rate of infection (2.6% vs 2.8%; p=0.17). However, Group B had significantly lower infection among the clean contaminated procedures (6.9% vs 7.7%; p=0.03) and overall (4.1% vs 4.9%; p=0.04). Conclusion: The high rate of infection demonstrated in patients receiving placebo indicates a need for routine chemoprophylaxis for SSI. A single dose of Cefuroxime at induction seems to work at least as well or better than triple regime and is the recommended prophylaxis.